Kajian Teknis Geometri Peledakan dan Powder Factor Terhadap Fragmentasi di PT Semen Padang Indarung - Jimmy Irawan; Irvani Irvani; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
This research is studying about rock fragmentation from blasting result in Front Existing PT Semen Padang Sumatera Barat which shows that there are unmatch size of blasting fragmentation from its target appointed by PT Semen Padang. This research is also study about blasting geometry that represent in burden value dan powder factor which used in the process. The methods used are quantitative and qualitative, that are by studying blasting geometry and powder factor from field observation result and calculating blasting fragmentation size which generated by Software Split- Desktop V.2.0. Blasting fragmentation size analysis in Front Existing is done by applying 4 m burden value, average fragmentation result as much 27.74 cm, and with 4.5 m burden value result as much 30.34 cm, and then with 5 m burden value result as much 29.26 cm while the effect of powder factor against rock fragmentation size in the research obtained using powder factor value as much 0.34 kg/m3, average fragmentation result in 27.6 cm, and with 0.37 kg/m3 powder factor resulting average fragmentation in 32.29 cm, and then with 0.44 kg/m3, the average fragmentation result as much 53.83 cm. Blasting recommendation that can be applied by looking at the research result is that using 4 m burden value to get average fragmentation size as much 27.74 cm, and powder factor value that is usable as much 0.34 kg/m3 in order to get 27.6 cm average fragmentation size